The Transformation of Gala and Mawah Towards the Bank Gala Sharia Microfinance Model in Aceh (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
The people of Aceh have traditional economic practices of gala (pawn) and mawah (profit sharing). However, traditional gala practices are often exploitative and contrary to sharia because lenders have full control of the collateralized productive assets. On the other hand, the potential of mawah as a cooperation scheme has not been optimized. This qualitative research analyzes how these two practices can be transformed into sustainable Islamic microfinance institutions, with case studies on practices that still exist in Southwest Aceh. Data were gathered through observation and interviews. The results of the study show that KSPPS Baitul Qiradh Gala Muamalah, or "Bank Gala" took the initiative to revitalize local wisdom with sharia principles. A fundamental transformation occurs in the practice of gala, where "Bank Gala" applies the rahn (sharia pawn) contract. This institution only holds a guarantee, while productive assets such as rice fields are still managed by their owners. This allows farmers to continue to work and earn income. For working capital financing, a mudharabah (profit sharing) contract with a flexible post-harvest return system is used. The "Bank Gala" model has proven to be successful in transforming harmful practices into fair, empowering farmers, and sharia-compliant transactions. This initiative has an impact on the success of the adaptation of tradition into a pillar of the modern economy rooted in local culture, as well as a model for sustainable community economic development.
Keywords: Gala; Mawah; Bank Gala; Economy Heritage